2023
DOI: 10.3390/jof9010119
|View full text |Cite
|
Sign up to set email alerts
|

High Incidence of Candidemia in Critically Ill COVID-19 Patients Supported by Veno-Venous Extracorporeal Membrane Oxygenation: A Retrospective Study

Abstract: Background: The incidence of candidemia in severe COVID-19 patients (0.8–14%) is two- to ten-fold higher than in non-COVID-19 patients. Methods: This retrospective analysis aimed to analyse the incidence of bloodstream infections (BSI) due to Candida in a cohort of COVID-19 patients supported with ECMO. Results: Among 138 intubated and ventilated patients hospitalized for ≥10 days in the intensive care unit of a teaching hospital, 45 (32.6%) patients received ECMO support, while 93 patients (67.4%) did not mee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
1
0
Order By: Relevance
“…Furthermore, in non-COVID-19 patients on ECMO in our institution, the incidence of candidemia was only slightly higher than in the general ICU population (4.8% versus 3.3%) [30]. Of note, we observed a much lower incidence of candidemia than that reported by Alessandri et al (9.32% versus 35.6%) [14].…”
Section: Discussioncontrasting
confidence: 65%
See 3 more Smart Citations
“…Furthermore, in non-COVID-19 patients on ECMO in our institution, the incidence of candidemia was only slightly higher than in the general ICU population (4.8% versus 3.3%) [30]. Of note, we observed a much lower incidence of candidemia than that reported by Alessandri et al (9.32% versus 35.6%) [14].…”
Section: Discussioncontrasting
confidence: 65%
“…COVID-19 might also induce the breakdown of mucosal barriers, such as in the lung or intestines. It is speculative whether this explains the higher incidence of candidemia in COVID-19 patients on ECMO, compared to COVID-19 patients not on ECMO, as reported by Alessandri et al [14]. We believe that it is not ECMO itself that is causing candidemia, as in our multivariable regression analysis, time on ECMO before IFD was not associated with IFD.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…We assumed that patients receiving ECMO treatment may require more analgosedation, a more intense anticoagulation, and may be sicker overall. For instance, studies reported higher infection rates among patients who were ECMO-treated compared to patients who were non-ECMO-treated [ 32 , 33 , 34 ]. Moreover, we observed a longer treatment duration in the ECMO subgroup.…”
Section: Discussionmentioning
confidence: 99%